Evaluate the effect of different mmps inhibitors on adhesive physical properties of dental adhesives, bond strength and mmp substarte activity - Pei Zheng (Nature Portfolio, 2017)
Abstract We have evaluated and compare the effect of different exogenous MMP inhibitors on adhesive physical properties of dental adhesives, bond strength, micro permeability and MMP substrate activity. 180-grit Sic paper was used to obtain the superficial dentin surface from each and every tooth after the wet grinding procedure. Dentin was exposed to four different MMP inhibitors to evaluate the effect on resin adhesive dentin interface. The four groups used in study were: 2% chlorhexidine digluconate, 2% doxycycline solution, 5% Proanthocyanidin (PR), Control Group. We evaluated and compared the four groups at each and every step of etching, bonding and resin application. Then, the immunolabeling was done with the help of the secondary antibodies with the pH of 7 and the dilution of 1:20. Amongst all the etching pretreatment groups, CHE group (Chlorhexidine etching group) revealed highest exposure to collagen fibrils than the other groups of etching. Then after the CHE group, the next group which has the second highest exposure DOE group. MMP inhibitor application for time duration of 1 minute after the etching procedures significantly improves the bond strength, exposure to collagen fibres and uniforms the dense form of dentin hybrid layer.